Pemanfaatan Sistem Informasi Geografi untuk Pemetaan Kawasan Produksi Komoditas Unggulan Tanaman Buah-buahan Tahunan di Kabupaten Tanah Datar - Wulandari, Dina; Syarief, Azhari (Lembaga Yasin AlSys, 2024)
Village area development planning is closely related to the agricultural sector. The development of superior fruit horticultural commodities can utilize Geographic Information Systems (GIS). This research aims to identify superior annual fruit crop commodities in Tanah Datar Regency and map the production areas of these commodities. This research is quantitative descriptive, where superior products are determined through Location Quotient (LQ) analysis, while production area mapping uses Getis-Ord Gi* Hot Spot analysis at the sub-district level. The results of the analysis show that the leading commodity for fruit crops in Tanah Datar Regency is avocado. The Getis-Ord Gi* Hot Spot analysis shows that the location of the leading area with the highest spatial production value is in Lintau Buo District, with commodities such as star fruit, duku, lemon, longan, mango and pineapple.